Image enhancement technique based on improved PSO algorithm - Gao Qinqing; Zeng Guangping; Chen Dexin; He Ketai (2011 6th IEEE Conference on Industrial Electronics and Applications, 2011)
In this paper, image enhancement is considered as an optimization problem and improved PSO(Particle Swarm Optimization) is used to solve it. Also in it, parameterized transformation function is used, which uses global and local information of the image. And an objective criterion for measuring image enhancement - taking fully consideration of the entropy of the image and edge information - is proposed. The main job of this paper tries to achieve the best image enhancement function with the help of improved PSO - parameters optimization. Results have been proved out better compared with other enhancement techniques, such as HE(Histogram Equalization), LCS(Linear Contrast Stretching) and GAIE(Genetic Algorithm based on Image Enhancement).